1981
DOI: 10.1037/0735-7028.12.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Training in medical psychology: A survey of graduate and internship training programs.

Abstract: American Psychological Association-approved doctoral and internship programs in clinical and counseling psychology were surveyed regarding training opportunities in medical psychology. A total of 42 graduate and 65 internship programs responded. Survey resultsindicated that the majority ofboth types of programs offered didactic and experiential training, including diagnostic and therapeutic activities with a wide variety of medical/ surgical patients. There appears to be a sufficient number of faculty psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…At this time, minimal qualifications or guidelines for adequate preparation have not yet been established (Degood, 1979). Thus training in a traditional graduate psychology program may be inadequate for the type or variety of roles assumed in a pain center (Gentry, Street, Masur, & Asken, 1981; Grezesiak, 1979; Olbrisch & Sechrist, 1979). Because of the specific training needs of psychologists in behavioral medicine, which may not be provided in the traditional psychology doctoral programs, there have in fact been some efforts in designing a specialized program for health psychologists (Stone, 1979).…”
mentioning
confidence: 99%
“…At this time, minimal qualifications or guidelines for adequate preparation have not yet been established (Degood, 1979). Thus training in a traditional graduate psychology program may be inadequate for the type or variety of roles assumed in a pain center (Gentry, Street, Masur, & Asken, 1981; Grezesiak, 1979; Olbrisch & Sechrist, 1979). Because of the specific training needs of psychologists in behavioral medicine, which may not be provided in the traditional psychology doctoral programs, there have in fact been some efforts in designing a specialized program for health psychologists (Stone, 1979).…”
mentioning
confidence: 99%
“…Clinical Psychology professional growth escalated with its empirically developed assessment and treatment interventions. The initial invitations in Medicine came to Psychologists from departments of Psychiatry [1][2][3]. The recognition of the knowledge competencies (i.e., Brain & Behavior, Social Interactions, Learning, Memory, Perception) fundamental to the training of doctoral level Clinical Psychologists expanded to the Veteran's Administration service and medical specialties of Neurology and Physical Medicine [4].…”
Section: Extending Clinical Practice To Medicinementioning
confidence: 99%
“…Only 28% of these programs reported prevention (health promotion) emphases as offerings. Additionally, results of a survey of APA-approved clinical psychology predoctoral internships suggested that most trainees in clinical psychology also are exposed to medical psychology (Gentry, Street, Masur, & Asken, 1981).…”
Section: Current Programsmentioning
confidence: 99%